Ответы и объяснения

2013-05-11T13:19:01+04:00

-у=-10-3х                                                                  х²-40х-12х²-(100+60х+9х²)+20=0

x^2-4xy-y^2=-20                                                       х²-40х-12х²-100-60х-9х²+20=0

                                                                                  -20х²-100х-80=0(/-20)

у=10+3х                                                                    х²+5х+4=0

x^2-4x(10+3х)-(10+3х)^2=-20                               D=25-4*4=9

                                                                                   x=(-5+3)/2=-1

                                                                                  x=(-5-3)/2=-4

х=-1                х=-1

у=10+3*(-1)  у=7

х=-4                х=-4

у=10+3*(-4)  у=-2

                                       ОТВЕТ: (-1;7);(-4;2)